Debt: 5000 Years and Counting as It Was - Aleksandrova, Maria (Экономическая социология, 2018)
This article presents a review of a conference Debt: 5000 Years and Counting that took place at the University of Birmingham (Birmingham Research Institute for History and Cultures) on June 8–9, 2018. The conference was based on the recent influential book Debt: The First Five Thousand Years by David Graeber. The conference gathered representatives from all social sciences to discuss the understudied topic of history and ideology of debt. The review contains references to several papers discussed at the conference to give an idea of the approaches used in one way or another in many of the papers. The papers discussed in the review were devoted to the boost of micro-credit in Latvia after the 2008 global financial crisis, the ideology of trapped equity that led to this crisis, the attempt to resolve confusion between the view that debts are to be repaid and the view that profiting from lending is evil, credit in the Islamic Caliphate in the 7th to 10th centuries, the long durée of public debt since the Middle Ages to Early Modern times, and the royal debts in England in the middle of the 16th century. The conference was interesting not only because of the importance of the subject but also because of the originality of the format which helped make the event less hierarchical and less dominated by the academic elite. In addition, one of the aims of the conference was to combine academic and activist approaches. Among the participants there were a few activists. This experience is also described in the review.